Exploring the Use of TikTok as An Alternative Medium for Teaching English Grammar at Junior High School - Yuana Rahmaniah; Khusnul Khotimah; Dzul Rachman (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study directly addresses the lack of engaging methods for teaching English grammar to junior high school students by exploring TikTok as an alternative medium for instruction. Employing a mixed methods approach, it combines a one-group pre-test and post-test experimental design with qualitative observations to assess both learning outcomes and student experiences. The participants were 25 eighth-grade students at SMP Negeri 17 Samarinda. They created group-based TikTok videos to explain assigned grammar tenses after completing a grammar pre-test. The findings revealed a significant improvement in grammar mastery, as confirmed by statistical analysis, and students demonstrated increased motivation, creativity, and collaboration. These results suggest that TikTok, when used with clear objectives and instructional support, can be a powerful supplementary tool for grammar learning.